NGHIÊN CỨU XÂY DỰNG MÔ HÌNH ĐIỀU KHIỂN NHÀ THÔNG MINH SỬ DỤNG KẾT NỐI BLUETOOTH, GSM - Võ, Minh Phụng (DalatUniversity, 2023)
Smart home systems capable of connecting electrical equipment, interacting with the user to control devices of convenience, or operating according to a pre-installed schedule were investigated. In this study, the authors built a model smart home system capable of receiving signals from environmental sensors by connecting the electrical equipment in the house to a network through wireless technologies, such as Bluetooth and Global System Mobile (GSM). The devices are controlled via software on a smartphone. By understanding the existing smart home system and comparing the implemented solutions, the new technology is now more suitable. The authors have created a product model that meets the stated objectives: it is feasible for deployment in the smart house system, serves for routine operation by a family to add comfort, is modern, and is easy to install with reasonable costs.